Workshop on Participatory Research tools, Latin America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The training called 'regional workshop on participatory research for climate change and agriculture' took place in Matagalpa, Nicaragua the 10th until the 15th of November, 2014. Local partners were invited to receive training on participatory research methods and gender inclusion. The workshop included three days of field work practicing the newly learned tools.